Trans*legalities: Preliminary study of files on recognition of trans* identities in Peru - Zelada, Carlos J. (2017)
In the present text, the authors propose a novel methodology for the identification and analysis of the speeches made by plaintiffs and judges in cases of recognition of trans* identities. Both conclude that these actors converge in the process from rigid binary, pathologizing and genitalizing discourses, making very scarce references to the most recent contributions that Law and Social Sciences have made to the understanding of gender identity.